2018
DOI: 10.3389/fpsyt.2018.00134
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of an Anti-Aggression and De-Escalation Training on Ward Atmosphere and Subjective Safety May Depend on Previous Training Experience

Abstract: Anti-aggression and de-escalation (ADE) trainings of health-care professionals working on psychiatric inpatient wards have been shown to increase staff knowledge and confidence, which could be connected with higher subjective safety. Additionally, a potential reduction of aggressive incidents could improve ward atmosphere. Thus, the current study aimed to investigate the effects of ADE training on ward atmosphere and subjective safety. In 2015, an ADE training was established at the Psychiatric University Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
(23 reference statements)
0
14
0
3
Order By: Relevance
“…High fidelity was measured in an Australian study that found seclusion rates to be reduced by 36% after the Safewards implementation in psychiatric inpatient units (33). Further empirical evidence for reducing conflict and containment in psychiatry was found regarding several multi-perspective conflict-reduction interventions focusing on leadership, staff, and patient level (18, 37, 38). Richter and Needham (18), e.g., showed that participating in de-escalation and aggression management staff training can lead to better knowledge and a more precise documentation of conflicts and containment.…”
Section: Introductionmentioning
confidence: 99%
“…High fidelity was measured in an Australian study that found seclusion rates to be reduced by 36% after the Safewards implementation in psychiatric inpatient units (33). Further empirical evidence for reducing conflict and containment in psychiatry was found regarding several multi-perspective conflict-reduction interventions focusing on leadership, staff, and patient level (18, 37, 38). Richter and Needham (18), e.g., showed that participating in de-escalation and aggression management staff training can lead to better knowledge and a more precise documentation of conflicts and containment.…”
Section: Introductionmentioning
confidence: 99%
“…Open-door policies have been associated with an improved ward atmosphere (7,(35)(36)(37). Patients and HCP in our study reported improved well-being and improved establishment of therapeutic relationships due to decreasing control functions after opening the ward.…”
Section: Category Quotesmentioning
confidence: 57%
“…Another study also found that nurses receiving DE training possessed greater self-perceived confidence than those without, demonstrating that this form of preparation effectively enhanced nurses' performances by strengthening their confidence levels in dealing with WPV [41]. In addition, Fröhlich et al, [42] highlighted DE training's role in helping to cultivate a harmonious atmosphere within psychiatric wards by improving patients' coherence and subjective safety. Most importantly, the application of DE techniques decreases the use of coercive strategies.…”
Section: Introductionmentioning
confidence: 97%